2023
DOI: 10.1002/adom.202300455
|View full text |Cite
|
Sign up to set email alerts
|

Triplet–Triplet Annihilation Enhanced Deep‐Blue Organic Light‐Emitting Diodes by Naphtho[1,2‐d]imidazole‐Isomer Derivatives with Spin–Orbit Coupling

Guo‐Xi Yang,
Deng‐Hui Liu,
Qing Gu
et al.

Abstract: The utilization of triplet excitons is of great importance for organic light‐emitting diodes (OLEDs). Triplet–triplet annihilation (TTA) is one of the effective tactics to achieve high efficiency deep‐blue organic electroluminescence emitters by converting two triplet excitons into one singlet exciton. Whereas, in addition to the 25% electrogenerated singlet excitons, the proportion of radiative singlet excitons (RSE) produced by the TTA process is usually only 15%; thus the total radiative excitons are 40%. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…Because of the higher emission energy, the operational lifetime of blue OLEDs is much shorter than that of green and red ones. Various emitters and device structures have been developed to improve the efficiency and lifetime of blue OLEDs. However, because of the low reverse intersystem crossing (RISC) rate of a multiresonance thermally activated delayed fluorescence (MR-TADF) emitter, the device operational lifetime of the narrow FWHM blue emitters is still unsatisfactory. Thus, realizing stable and narrow FWHM blue OLEDs is still a challenge and has important meaning.…”
Section: Introductionmentioning
confidence: 99%
“…Because of the higher emission energy, the operational lifetime of blue OLEDs is much shorter than that of green and red ones. Various emitters and device structures have been developed to improve the efficiency and lifetime of blue OLEDs. However, because of the low reverse intersystem crossing (RISC) rate of a multiresonance thermally activated delayed fluorescence (MR-TADF) emitter, the device operational lifetime of the narrow FWHM blue emitters is still unsatisfactory. Thus, realizing stable and narrow FWHM blue OLEDs is still a challenge and has important meaning.…”
Section: Introductionmentioning
confidence: 99%
“…Thereafter, electrons can be transferred from the excited T 1 to the S 1 (when the E S1‑T1 < 0.2 eV), thereby increasing the S1 population from 25 to 100% and consequently overcoming the 5% external quantum efficiency (EQE) barrier of prompt fluorescence. TADF, however, is slower than direct fluorescence and depends on a material with efficient charge transfer (CT) abilities and a high potential for triplet exciton quenching due to the long lifetimes. , Deep-blue and blue-fluorescent organic emitters, such as those based on anthracene and pyrene derivatives, have also shown improved internal efficiencies beyond 25% by harnessing triplet–triplet annihilation (TTA) and their efficient spin–orbit coupling. …”
Section: Introductionmentioning
confidence: 99%
“…The selective cytotoxicity toward cancer cells and the fluorescence of naphtho­[1,2- d ]­imidazoles make possible the application of these compounds in antitumor theranostic systems . It was also found that naphtho­[1,2- d ]­imidazole derivatives are promising light-emitting materials for OLEDs. Naphtho­[1,2- d ]­imidazoles are usually synthesized by condensation of carbonyl compounds with 1,2-diaminonaphthalene derivatives, ,, often formed in situ. , Intramolecular condensation of 1-amido-2-amino/1-amino-2-amido-naphthalenes is also frequently used. ,,,, Another approach involves the cyclization of 1-aminonaphthalene derivatives containing an N-CRN moiety. In all of the mentioned methods, the assembly of the tricyclic naphtho­[1,2- d ]­imidazole skeleton is completed by the formation of the imidazole ring (imidazole ring-forming strategy) (Scheme , (1a)). Only one compound of this series, 3-methyl-3 H -naphtho­[1,2- d ]­imidazole, was synthesized according to another scheme, involving the formation of the internal benzene ring at the last step (benzene ring-forming strategy) (Scheme , (1b)).…”
Section: Introductionmentioning
confidence: 99%